Headache with occipital neuralgia phenotype: Report of four cases - Vanesa Nagel; Lucas Bonamico; María T Goicochea (SAGE Publishing, 2021)
Background: The International Headache Society defines Occipital neuralgia as an unilateral or bilateral paroxysmal, shooting or stabbing pain in the posterior part of the scalp, in the distribution(s) of the greater, lesser and/or third occipital nerves. The most common pain trigger in this area result from chronically contracted muscles. Different aetiologies of headache with occipital neuralgia phenotype have been described. Case: We report four cases in which pain with occipital neuralgia phenotype was the initial symptom of a clivus chordoma; a para-pharyngeal carcinoma; a vertebral dissection; and a brachial plexitis due to zoster. Conclusion: A detailed anamnesis and physical examination should be performed in these patients. If during follow up atypical finding appears, we recommend head and neck gadolinium-enhanced MRI and biochemistry to exclude secondary causes.